Limitation of Technical Error in Government Regulations Towards E-Commerce Trade Regarding Validity Electronic Contracts - Putu Tissya Poppy Aristiani; I Made Sarjana (University of Udayana, 2024)
This study is aimed to investigate the multiple interpretations form boundaries that appears from the understanding of the phrase “technical error” in Government Regulation related to tradethrough e-commerce on the electronic contract’s legitimacy and to inspect the legal protection towards business owners, system makers, and recipients of goods/services. This study utilized a normative juridical mechanism with a statutory and analytical approach. The results demonstrate that the technical error phrase in Article 57 paragraph (2) of Government Regulation No. 80 of 2019 composed the implication of default, subsequent in the electronic contract being null and void. Article 6 of Law No. 8 of 1999 includes legal protection availability towards business owners in such scheme of self-defense guarantees for when a dispute arises with consumers who had bad intentions. Article 40 of Law No. 28 of 2014 explained in detail that computer programs were one of the protected copyrighted works and it was an act of legal protection towards the makers of the systems. Towards the justice guarantees in relation to the recivied quality, legal protection towards goods/services’ recipients is confined in Article 46 of Law No. 8 of 1999.